Xylooligosaccharides from Industrial Fruit and Restaurant Waste Produced by Liquid Hot Water Treatment - Pereira, Beatriz Salustiano [UNESP]; Freitas, Caroline de [UNESP]; Masarin, Fernando [UNESP]; Brienzo, Michel [UNESP] (Springer Nature, 2022)
Agro-industrial and food waste generation are increasing and alternatives are necessary for better use of these biomasses, such as conversion by liquid hot water (LHW), due to environmental and economic advantages. Moreover, it could be an alternative for the treatment of lignocellulosic biomass to produce xylooligosaccharides (XOS) and other value-added products. This study evaluated the production of XOS via LHW of industrial fruit and food waste. The application of LHW treatment showed a maximum of 32.60% XOS and 5.07% of xylose with banana peel residue, 8.21% of XOS and 1.99% of xylose with guava bagasse, 67.01% XOS and 4.02% xylose with orange bagasse, and 33.42% XOS and 2.56% xylose with restaurant residue. The results showed that the ideal conditions to obtain XOS are by using a high temperature and a low reaction time (160 °C and 15 min) for banana peel residue, a high temperature and medium time (172.43 °C and 35 min) for guava bagasse, a medium temperature and time for orange bagasse (130 °C and 35 min), and for restaurant waste, a medium temperature and a low reaction time (130 °C and 6.72 min). The best residue was orange bagasse with potential XOS production of 208 kg per ton of the material. This study determined LHW conditions that maximized XOS production with a low amount of xylose and degradation products, probably with no need for purification. However, attention is needed for the extractives to be solubilized with the LHW treatment of industrial fruit and food waste.
Keywords: Agro-Industrial Waste; Autohydrolysis; Biomass; Degradation Products; Prebiotic